Estimasi Nilai Ripitabilitas Berat Badan Kambing Peranakan Ettawa Di Balai Pembibitan Ternak Unggul Dan Hijauan Pakan Ternak Pelaihari Kalimantan Selatan - Sumadi, Sumadi; Annisa, Alfiona; Baliarti, Endang; Fathoni, Akhmad (2018)
Peranakan Ettawa (PE) Goat was a type of goat that widely maintained in Indonesia. The value of repetition of a trait in PE Goat could be determined by calculating the value of the ripitability. This study aimed to estimate the ripitability value of birth weight, weaning weight and yearling weight of PE inBalai Pembibitan Ternak Unggul dan Hijauan Pakan Ternak Pelaihari, South Kalimantan. The material used in this study was growth record and pedigreerecord in 2015 and 2016. The ripitability value was estimated using the between class correlation method and intra classcorrelation method. The results showed that the value of ripitability of birth weight, weaning weight, and yearling weight analyzed using between classes correlation method were 0.31 ± 0.08; 0.21 ± 0.11; and 0.41 ± 0.14, respectively. The value of ripitability calculated by intra class correlation method of birth weight, weaning weight, and yearling weight were 0.08 ± 0.01; 0.03 ± 0.01; and 0.08 ± 0.04 respectively. The conclusion was the value of ripitability includes the low, medium and high categories. A trait with high value of ripitability (yearling weight) can be recommended to be used in calculating the value of MPPA.